Sintesis Nanosilika dari Sekam Padi Menggunakan Metode Sol Gel dengan Pelarut Etanol - Arenst Andreas; Hans Kristianto; Devi Fitriani Kurniawati (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Rice husk is a byproduct of the milling process of paddy into rice. Silica can be obtained from rice husk to be utilized in various fields in the industry into high value products, one of them is nanosilica. Nanosilica can be obtained from rice husk using sol gel method with ethanol solvent. Before using sol gel method, performed insulating silica from rice husk using leaching method with citric acid solvent and combustion method. The purpose of this research is to study the effects of feed ratio (sodium silica): solvent (ethanol) and aging time on sol-gel method on the physical characteristics and morphology of nanosilica. Variations were made in the sol-gel method consists of variations in the volume of sodium silica: ethanol is 1: 9, 1:16, and 1:23. Moreover, variations of aging time is 1, 3, and 7 days. Characteristics of nanosilica were analyzed using SEM (Scanning Electron Microscope) + EDX (Energy Dispersive X-Ray) and XRD (X-Ray Diffraction). At variations of ethanol solvent, the best variety is 1:16 for providing the highest purity silica (56.85%). While at the time variation of aging, aging time for 7 days giving highest silica purity results and the smallest size diameter.